Improvement and application of recommended food score for hypertension in Korean adults: the Korean Genome and Epidemiology Study - Hwang, Jiyoung; Kim, Jeongsu; Kim, Hyesook (Frontiers in Nutrition, 2024)
Background Addressing dietary factors to lower blood pressure can be a crucial strategy at the population level to mitigate the risk of hypertension. In a prior investigation, a tailored food score was used as a dietary index relevant to hypertension among Korean adults. This current study aims to assess the association between the overall quality of the diet, taking into account more precise food components, and evaluate the risk of developing hypertension. Methods This prospective cohort study included 5,342 adults aged 40–70 without hypertension who participated in the Korean Genome and Epidemiology Study (KoGES) from 2001 to 2016. The improved Recommended Food Score for Hypertension (iRFSH) is a modified version of the Recommended Food Score to assess the consumption of foods recommended in the Dietary Approaches to Stop Hypertension (DASH) diet for Korean foods. A higher score reflects greater consumption of recommended foods, indicative of higher dietary quality. The maximum total score is 65. High blood pressure, which includes both hypertension and prehypertension, was analyzed using Cox proportional hazard regression models to examine its prospective relationship with iRFSH. Results Among 2,478 males and 2,864 females with 10.8 mean years of follow-up, a higher score of iRFSH was associated with a lower risk of hypertension in the highest quintile compared to the lowest quintile [total: hazard ratio (HR): 0.79; 95% confidence interval (CI): 0.72, 0.87; female: HR: 0.71; 95% CI: 0.62, 0.83]. Conclusion Higher iRFSH is associated with a lower incidence of hypertension. Our results suggest that the iRFSH may be a potential tool for assessing dietary quality and dietary patterns and predicting the risk of hypertension in Korean adults.